Safety and validity of extracorporeal fenestration and in situ fenestration in patients with aortic disease involving the left subclavian artery: a prospective, single-center, randomized controlled study - Xiaojian Jia; Jingjin Wu; Caiyou Ding; Yanbo Lou (Trials)
Abstract Background Thoracic aortic pathologies involving the aortic arch are a great challenge for vascular surgeons. Maintaining the patency of supra-aortic branches while excluding the aortic lesion remains difficult. Thoracic EndoVascular Aortic Repair (TEVAR) with fenestrations provides a feasible and effective approach for this type of disease. The main purpose of this trial is to assess the safety and validity of extracorporeal fenestration and in situ fenestration in patients with aortic disease involving the left subclavian artery. Methods This is a prospective, single-center, randomized controlled study. A total of 170 eligible patients will be recruited from The Fourth Affiliated Hospital, Zhejiang University School of Medicine in China and randomized on a 1:1 basis either to the group A (extracorporeal fenestration) or the group B (in situ fenestration). The primary outcome will be the all-cause mortality (30 days). The secondary outcomes will include incidence of secondary intervention (30 days, 6 months, 1 year), incidence of endoleak (30 days, 6 months, 1 year), incidence of major adverse events (MAE) (i.e., immediate procedural success and complications) (30 days, 6 months, 1 year), immediate technical success rate, and all-cause mortality (6 months, 1 year). Discussion Suppose extracorporeal fenestration non-inferior to in situ fenestration in patients with aortic disease involving the left subclavian artery. This trial aims to demonstrate the safety and validity of extracorporeal fenestration and in situ fenestration in patients with aortic disease involving the left subclavian artery, which is expected to provide a reference for Thoracic EndoVascular Aortic Repair (TEVAR) with fenestrations. Trial registration ClinicalTrials.gov NCT06256757. Registered on February 5, 2024. https://clinicaltrials.gov/study/NCT06256757 .